Thrombin generation by calibrated automated thrombography in goat plasma: Optimization of an assay. Issue 8 (21st November 2021) - D'Alessandro, Elisa; Scaf, Billy; van Oerle, René; van Nieuwenhoven, Frans A.; van Hunnik, Arne; Verheule, Sander; Schotten, Ulrich; ten Cate, Hugo; Spronk, Henri M. H.
Abstract: The goat model of atrial fibrillation (AF) allows investigation of the effect of AF on coagulation. However, assays for goat plasma are not available from commercial sources. Calibrated automated thrombography (CAT) provides a global view of the coagulation profile by assessing in vitro thrombin generation (TG). We describe the customization of the CAT assay in goat platelet‐poor plasma (PPP) and in factor Xa (FXa)‐inhibitor‐anticoagulated PPP. TG was initiated in the presence of phospholipids and either (a) PPP reagent, reagent low, or reagent high; (b) goat brain protein extraction (GBP); or (c) Russell's viper venom‐factor X activator (RVV‐X). Contact activation was assessed by adding corn trypsin inhibitor. Different concentrations of prothrombin complex concentrate (PCC) were used to determine the sensitivity of both the GBP and RVV‐X method. To obtain FXa‐inhibitor anticoagulated plasma, rivaroxaban was added to plasma. TG settings with human reagents were not suitable for goat plasma. TG triggered with GBP increased peak height and ETP values. Similarly, the RVV‐X method produced comparable TG curves and was more sensitive to PCC titration. Finally, both methods were able to detect the decrease in clotting potential induced by FXa inhibition. This is the first study that reports the customization of the CAT assay for goats. The GBP and RVV‐X methods were comparable in triggering TG in goat plasma. The RVV‐X method seemed to better discriminate changes in TG curves due to increases in clotting potential as well as to FXa inhibition by rivaroxaban in goat plasma.